2016
DOI: 10.20533/licej.2040.2589.2016.0311
|View full text |Cite
|
Sign up to set email alerts
|

How Literature Circles Support EFL College Students’ Literary and Literacy Learning in a Children’s and Adolescent Literature Course

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Contrastingly, her point of view from the interview highlighted her increased personal interest in autonomous meaning making. This corroborates Su and Wu (2016) in that the assigned roles within the framework of literature circles can motivate EFL tertiary learners to be more responsible for the development of their own reading and writing repertoire.…”
Section: Individual Accountabilitysupporting
confidence: 82%
“…Contrastingly, her point of view from the interview highlighted her increased personal interest in autonomous meaning making. This corroborates Su and Wu (2016) in that the assigned roles within the framework of literature circles can motivate EFL tertiary learners to be more responsible for the development of their own reading and writing repertoire.…”
Section: Individual Accountabilitysupporting
confidence: 82%
“…According to Su and Wu (2016), literature circles can provide students with a safe and low-risk environment to experience dynamic interactions among readers and texts and can nurture the pleasure of reading literature and literacy skills simultaneously. The research results are consistent with the conclusion by Smith and Feng (2018) that literature circles could encourage students to read more and actively participate in group discussions with their peers.…”
Section: Resultsmentioning
confidence: 99%
“…Sociocultural Theory, which argues that cultural context, as well as social, material, and learning environments mediate human cognition and behavior, supports RC (Lantolf et al, 2015). Su and Wu (2016) found that RC created a low-risk, comfortable setting that motivated university students to read independently and then explore the texts in collaborative discussions. RC are also supported by the Reader-Response Theory, which affirms the importance of the reader and argues that different readers interpret the same text differently.…”
Section: Theoretical Frameworkmentioning
confidence: 99%